Effects of physical activity as an adjunct treatment on healing outcomes and recurrence of venous leg ulcers: A scoping review. Issue 2 (10th February 2022) - Qiu, Yunjing; Osadnik, Christian R.; Team, Victoria; Weller, Carolina D.
Abstract: Healing time is protracted and ulcer recurrence is common in patients with venous leg ulcers. Although compression is the mainstay treatment, many patients do not heal timely. Physical activity may be a clinically effective adjunct treatment to compression to improve healing outcomes. This scoping review provides a broad overview of the effect of physical activity as an adjunct treatment to compression on wound healing and recurrence. We followed the six‐step framework developed by Arksey and O'Malley. We searched electronic databases and trial registration websites for relevant studies and ongoing trials. Two authors independently screened and selected articles. Findings were presented in a descriptive statistical narrative summary. We consulted and presented our findings to the wound consumer group to ensure the relevance of our study. Physical activity interventions in 12 out of the 16 eligible studies consisted of only one component, eight studies were resistance exercises, three studies reported ankle and/or foot range of motion exercises, and one study reported aerobic/walking exercises. The remaining four studies involved multicomponent exercise interventions. Resistance exercise combined with ankle and/or foot range of motion exercise minimised ulcer size on day 12 (intervention group: 4.55 ± 1.14 cm 2 vs. control group: 7.43 ± 0.56 cm 2 ) and improved calf muscle pump performance on day 8 (ejection fraction: 40%–65%; residual volume fraction: 56%–40%). We identified one study that reported ulcer recurrence rate with no clinical difference in the intervention group versus the control group (i.e., 12% in intervention vs. 5% in control). Our review identified that resistance exercise was the most common type of physical activity intervention trialled in the published literature. Resistance exercise combined with ankle and/or foot range of motion exercise appears to be effective adjunct treatments; however, the overall evidence is still relatively weak as most programmes had a short intervention period which limited clinical outcomes.